2010
DOI: 10.3748/wjg.v16.i31.3905
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized controlled trial evaluating cap-assisted colonoscopy vs standard colonoscopy

Abstract: CAC did not significantly different from SC in term of cecal intubation time and polyp detection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 23 publications
0
66
1
1
Order By: Relevance
“…Three studies including 2 prospective RCTs [7,8] and 1 retrospective study [9] , all from Germany describing the EC were included for the review. Six prospective RCTs, 1 each from Germany [10] , Hong Kong [11] , Netherlands [12] , US [13] , South Korea [14] , Australia [15] and 1 retrospective study from Hong Kong [16] describing the CAC were included for the review. One multicenter (Netherlands, Israel and US) RCT describing ERC was also included [17] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies including 2 prospective RCTs [7,8] and 1 retrospective study [9] , all from Germany describing the EC were included for the review. Six prospective RCTs, 1 each from Germany [10] , Hong Kong [11] , Netherlands [12] , US [13] , South Korea [14] , Australia [15] and 1 retrospective study from Hong Kong [16] describing the CAC were included for the review. One multicenter (Netherlands, Israel and US) RCT describing ERC was also included [17] .…”
Section: Resultsmentioning
confidence: 99%
“…In the prospective studies, the study subjects were grouped into 2 arms based on the type of intervention: EC [7][8][9] or CAC [10][11][12][13][14][15] or ERC [17] versus standard colonoscopy (SC), regular colonoscopy (RC) or conventional colonoscopy (CC). The retrospective studies looked into the EC [9] and CAC [16] performed.…”
Section: Type Of Colonoscopy and Technical Aspectmentioning
confidence: 99%
See 1 more Smart Citation
“…al. 10 in 400 subjects, reported that there was no significant polyp detection rate difference detection standard colonoscopy and cap-assisted colonoscopy (31.3% vs. 32.8%, respectively). Recently, a rearward viewing device was introduced for use during colonoscopy with standard endoscopes.…”
Section: Introductionmentioning
confidence: 96%
“…Most of the studies did not report the level of training of the fellow, which has been shown in some studies, but not others, to correlate with higher ADR [6][7][8]. Finally, three studies reported PDR but not ADR, which limits the conclusions one can draw from these studies [9][10][11].…”
mentioning
confidence: 94%